2019
DOI: 10.1186/s12859-019-2825-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic genome-scale cell-specific metabolic models reveal novel inter-cellular and intra-cellular metabolic communications during ovarian follicle development

Abstract: Background The maturation of the female germ cell, the oocyte, requires the synthesis and storing of all the necessary metabolites to support multiple divisions after fertilization. Oocyte maturation is only possible in the presence of surrounding, diverse, and changing layers of somatic cells. Our understanding of metabolic interactions between the oocyte and somatic cells has been limited due to dynamic nature of ovarian follicle development, thus warranting a systems approach. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…To compare the transcriptome profile of somatic cells from follicles co-cultured in vitro to those from freshly isolated follicles in vivo at comparable stages of development, we drew on previously published data available online on the Gene Expression Omnibus (GSE 97902) 33 – 35 . This published dataset was used to develop a metabolic model for murine ovarian follicles by updating the previously published dataset Mouse Recon 1 to include human homologues and key ovarian follicle development pathways that were not previously represented 33 , 36 . The dataset used during model development includes transcriptome data from the follicular structure as a whole (including the oocyte and somatic cells) at various stages of follicle development 33 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the transcriptome profile of somatic cells from follicles co-cultured in vitro to those from freshly isolated follicles in vivo at comparable stages of development, we drew on previously published data available online on the Gene Expression Omnibus (GSE 97902) 33 – 35 . This published dataset was used to develop a metabolic model for murine ovarian follicles by updating the previously published dataset Mouse Recon 1 to include human homologues and key ovarian follicle development pathways that were not previously represented 33 , 36 . The dataset used during model development includes transcriptome data from the follicular structure as a whole (including the oocyte and somatic cells) at various stages of follicle development 33 .…”
Section: Resultsmentioning
confidence: 99%
“…To compare the in vitro follicle culture data to previously published microarray data from freshly isolated follicles of different stages, raw expression data (GSE 97,902) from the Gene Expression Omnibus was downloaded using the package GEOquery 33 , 64 . This dataset reports ovarian follicle gene expression at various stages of development, using RNA collected from freshly isolated follicles from CD-1 mice 33 . From this dataset, the three replicates each of primary, multilayer secondary, and antral follicle transcriptome data were extracted for comparisons to the in vitro co-culture data.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the results of the present study indicated a difference of regulatory elements for the transition of reproductive processes between single lamb and prolific sheep. In addition, these differentially expressed genes were mostly enriched in several KEGG pathways, including metabolic pathway (Penalver Bernabe et al., 2019), ovarian steroidogenesis, steroid hormone biosynthesis and oestrogen signalling pathway. Moreover, these pathways play crucial roles in reproductive hormone biosynthesis and follicular development.…”
Section: Discussionmentioning
confidence: 99%
“…This mathematical platform along with the integration of omics data (genomics, transcriptomics, proteomics, metabolomics, etc.) has demonstrated usefulness in guiding experimental efforts and elucidating mechanisms affecting cell phenotypes in many different cell types [ 150 , 151 , 152 , 153 , 154 , 155 , 156 ].…”
Section: Genome-scale Modeling: a Suitable Platform For Improving mentioning
confidence: 99%